Beyond TNF: TNF superfamily cytokines as targets for the treatment of rheumatic diseases - Croft, Michael; Siegel, Richard M. (Nature reviews. Rheumatology, 2017)
Key Points TNF inhibitors are among the most effective protein-based drugs for reducing inflammation associated with several rheumatic diseases In addition to TNF, the TNF superfamily (TNFSF) comprises other ligand–receptor combinations that might participate in the pathogenesis of rheumatic disease TNFSF members initiate several processes, including immune activation, tissue inflammatory responses and cell death or suppression Many TNFSF proteins other than TNF are being evaluated in preclinical mouse or human studies as possible therapeutic targets in rheumatic diseases TNFSF members can be targeted to either restore tolerance in rheumatic diseases or to regulate tissue cell responses In this Review, the authors discuss the function of the TNF and TNF receptor superfamily, their role in rheumatic diseases such as rheumatoid arthritis and systemic lupus erythematosus, and how current knowledge is being translated into potential disease therapies. TNF blockers are highly efficacious at dampening inflammation and reducing symptoms in rheumatic diseases such as rheumatoid arthritis, psoriatic arthritis and ankylosing spondylitis, and also in nonrheumatic syndromes such as inflammatory bowel disease. As TNF belongs to a superfamily of 19 structurally related proteins that have both proinflammatory and anti-inflammatory activity, reagents that disrupt the interaction between proinflammatory TNF family cytokines and their receptors, or agonize the anti-inflammatory receptors, are being considered for the treatment of rheumatic diseases. Biologic agents that block B cell activating factor (BAFF) and receptor activator of nuclear factor-κB ligand (RANKL) have been approved for the treatment of systemic lupus erythematosus and osteoporosis, respectively. In this Review, we focus on additional members of the TNF superfamily that could be relevant for the pathogenesis of rheumatic disease, including those that can strongly promote activity of immune cells or increase activity of tissue cells, as well as those that promote death pathways and might limit inflammation. We examine preclinical mouse and human data linking these molecules to the control of damage in the joints, muscle, bone or other tissues, and discuss their potential as targets for future therapy of rheumatic diseases.